EFFECT OF PROVIDING FREE SPUTUM MICROSCOPY SERVICE TO PRIVATE PRACTITIONERS ON CASE NOTIFICATION TO NATIONAL TUBERCULOSIS CONTROL PROGRAM - Khan, Javaid Ahmad; Akbani, Farooq; Malik, Amyn; Kazi, Ghulam Nabi; Aslam, Fawad; Hussain, Syed Fayyaz (Journal of Ayub Medical College Abbottabad, 2005)
Background: This study was undertaken to see whether providing free sputum microscopy services to private practitioners helps in case notification to the national tuberculosis control program. The knowledge, attitudes and practices of these practitioners regarding tuberculosis were also evaluated. Methods: A questionnaire was administered to all the private practitioners practicing in a densely populated area of Karachi. They were asked to fill tuberculosis notification cards for the first three months and then for another three months when an incentive in the form of free sputum microscopy was provided to the practitioners. Results: Although the majority of the practitioners knew that cough, fever and weight loss are the main symptoms of tuberculosis, less than half knew that blood in sputum, poor appetite and chest pain could also be associated with tuberculosis. Only 66% of the practitioners indicated sputum microscopy as the preferred diagnostic method for tuberculosis. Only 50% of the practitioners self treated the patients, while the remaining half referred their patients to specialists. Around 80% of the practitioners were aware of the four first-line anti-tuberculosis drugs. Less than half of the practitioners considered sputum microscopy as the most useful follow-up investigation in a patient with pulmonary tuberculosis. Generally, there was a poor response in case notification by private practitioners on provision of free sputum microscopy. Conclusion: An overwhelming majority of the practitioners had poor knowledge concerning the correct treatment practices in Tuberculosis. Providing sputum free microscopy does not significantly help in improving tuberculosis case notification. Strategies for public-private collaboration in tuberculosis control are needed. Keywords: tuberculosis, private practice, sputum, microscopy, knowledge, attitude, behaviour, Pakistan.